Micro void coalescence of ductile fracture in mild steel during tensile straining - P. K. Pradhan; P. R. Dash; P. S. Robi; Sankar K. Roy (Fracture and Structural Integrity)
The ductile fracture occurs mainly in three stages i.e. void nucleation, void growth and the void coalescence. The present work focuses on the study the coalescence of existing micro void in a ductile material, mild steel. The specimen with holes in square array at various angle to load axis have been tested. The holes were machined in the specimen and assuming those hole as the voids. The growth and coalescence behaviours during tensile straining were observed both in macro and micro levels. Since the existing facility is not adequate to make hole size in micron, this work has been carried out by making hole upto 500 micron. The results are compared with other specimen with bigger size hole and without any hole. Also the effects of micro voids (present in the material) on the progress of crack have been studied. It is found that with same amount of voids, present in different positions, the mechanical properties of the material are altered.